Consideration of individual functional level and health status of war related above knee amputees - M. Masoumi; E. Esfandiari; A. Yavari; H. Saeedi; M. allami (Afarand Scholarly Publishing Institute, 2011)
Background and Purpose: There are two main goals in amputated persons: Enabling the person to walk, returning them into social environment. Adjusting to life with a prosthesis and other mobility technologies is a complex rehabilitation process. Unfortunately there is no information about individual functional level and health status for persons with limb loss to identify importance for rehabilitation programs . Purpose: consideration of individual functional level and health status in war related above knee amputees. Material and methods: For this study, 54 Iranian above knee amputees were examined according to 5-level functional classification system and asked to report their health status. Results: Pain or countralateral limb arthritis was reported in 77.77% , back pain in 74.07%, mental disorders in 55.55% of patients. 7.41% of patients were in level 1, 25.92%of patients were in level 2, 57.41% of patients were in level 3 and 9.26% were in level 4. Conclusion: according to this study, the most prevalent disorders were pain or countralateral limb arthritis, back pain and mental disorders. Also more than half of the amputees were in functional level 3 that the person has the ability or potential for ambulation with variable cadence.